(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This research was carried out to improve the teaching and learning process in order to get maximum results or learning achievements. In this case, the researcher wants to use the ADDIE instructional design with the Discovery Learning model. This research can be said as action research with experimental methods. The research sample is students who contract Education management courses in the odd semester of 2022/2023. The implementation of the research is the use of the ADDIE instructional design with the discovery learning model seen in each cycle and evaluation and improvements will be carried out in the next cycle. Based on the research results, it can be seen that ADDIE’s instructional design using the discovery learning model makes a positive contribution to improving student learning outcomes.